CIP2A regulates cancer metabolism and CREB phosphorylation in non-small cell lung cancer. Issue 1 (17th October 2014) - Peng, Bo; Lei, Ningjing; Chai, Yurong; Chan, Edward K. L.; Zhang, Jian-Ying
Abstract : Overexpression of CIP2A in lung cancer increased lactate production and CREB phosphorylation but decreased H2 O2 production. Abstract : The cancerous inhibitor of protein phosphatase 2A (CIP2A) is a recently characterized endogenous inhibitor of the phosphatase activity of protein phosphatase 2A (PP2A), which extends the half-life of oncogenic protein c-myc and promotes in vivo tumor growth. The function of CIP2A in cancer progression is still poorly understood. To uncover the underlying mechanism of CIP2A-mediated cell proliferation, we implemented a two-dimensional electrophoresis (2DE)-based proteomic approach to examine lung cancer cell H1299 with and without CIP2A. We found 47 proteins differentially expressed where 19 proteins were upregulated and 28 proteins were downregulated. These were categorized into functional groups such as metabolism (25%), transcriptional and translational control (23%), and the signaling pathway and protein degradation (20%). On one hand, we validate our proteomic work by measuring the metabolic change. The knockdown of CIP2A decreased the expression of LDH-A as well as the enzymatic activity, accompanying with a decreased lactate production, an increased NADH/NAD + ratio and ROS production. On the other hand, we found that CIP2A may regulate CREB activity through bioinformatics analysis. Our following experiments showed that, CIP2A positively regulated the phosphorylation of CREB in response to the serum treatment. Therefore, our proteomic study suggested that CIP2A mediates cancer progression through the metabolic pathway and intracellular signaling cascade.